Secrecy and Leadership: The Case of Theresa May's Brexit Negotiations. (2nd November 2019) - Heide, Marlen; Worthy, Ben
Abstract : Openness is essential for democratic leadership. It represents a moral commitment and an instrument for increasing trust and legitimacy. However, secrecy can still aid leaders by safeguarding their power and policies or preserving their reputation. This article examines Theresa May's attempted use of secrecy around the UK–EU Brexit negotiations to protect her power, policy, and reputation between 2016 and 2019. While this approach appeared successful initially, over time, the counter-pressure for openness reversed its benefits. By the beginning of 2019, it was clear that May's secrecy had limited her power, undermined her policy, and ultimately damaged her reputation. The analysis ends by drawing comparisons with Donald Trump, whose efforts to conceal his actions have produced the same counterproductive results. The case study illustrates how secrecy can create political space and bolster a leader's reputation in the short term; however, over time, secret-keeping encourages leaks and greater scrutiny, exposes policies, and damages reputations, especially in increasingly transparent governance systems such as in the United States and the UK. Context is key, and secrecy surrounding high-profile, controversial issues, such as Brexit, is difficult to preserve. It can prove particularly damaging when it is tied to the leader's reputation, as in May's case.